Performance of Multiple Borrowing Clients in Gandaki Province of Nepal (Prithvi Academic Journal, 2019)
The multiple borrowing problems are more common in microfinance institutions in Nepal. The study aims to evaluate the performance of multiple borrowing clients in Gandaki province of Nepal with reference to Muktinath Bikas Bank Limited (MBBL). The performance of multiple borrowing clients, in terms of women empowerment, consumption expenditure, capital expenditure, micro-enterprises creation, saving, investment, and profit, has been examined with the help of descriptive and inferential statistics. The study has been confined to five districts of Gandaki province and the data have been collected from MBBL clients who are involved in microfinance intervention at least from the last five or more years. The performance of most of the observed clients was empowered by microfinance activities but no significant difference in terms of changes in the livelihood parameters. Although microfinance programmes empower clients, the results of the investment, saving, micro-enterprises creation, capital and consumption expenditure, and income generation of clients are not convincing. The regulatory authority should identify the problems of multiple borrowing whether the financing from microfinance institutions is just for their profit or for productive application of loan. The socio-economic performance of clients is connected with the effective monitoring of clients made by microfinance institutions whether the loan has been properly utilized or not.